Syncretisms with the Nominal Complementizer1. (26th July 2017) - Baunaz, Lena; Lander, Eric
Abstract: Nominal complementizers (e.g. Eng. that, Fr. que ) often have the same morphophonological form as other grammatical items, such as demonstrative, relative, and wh‐pronouns. In this paper we treat such overlaps as instantiations of syncretism, and we discuss the different patterns of syncretism with the nominal complementizer in various languages. We treat the syncretism facts within a nanosyntactic framework (Starke2009, Caha2009 ), meaning that complementizers are not simplex heads of CP (or ForceP/FinP in Rizzi's1997 sense) but actually composed of multiple features, each feature corresponding to a head in a single functional sequence which is responsible for building demonstratives, complementizers, relativizers, and wh‐pronouns (for alternative decompositions of complementizers in Romance, Balkan, and Germanic, see also Baunaz2015, 2016, to appear Sanfelice & Poletto2014 ; and Leu2015, respectively). Interestingly, moreover, many of the languages under discussion show a bound morpheme appearing as an integral part of the internal morphological makeup of quantifiers. This bound morpheme may also be syncretic with the complementizer (Romance ‐ que /‐ che, Serbo‐Croatian ‐ što, Modern Greek ‐ ti, Finnish ‐ kin, and Hungarian ho‐ ) or not (Germanic ‐ thing /‐ ting, for which see also Leu2005 ). We call this the 'nominal core' ( n ), and its behavior with regard to syncretism is crucial for determining the hierarchical ordering of the functional sequence.